USE OF COLLOCATIONS IN ESSAY WRITING BY FOREIGN ARABIC LANGUAGE LEARNERS (Practitioner Research, 2023)
Several advancements are being made in the field of foreign language learning with the aim of facilitating the learning process and rendering it more accessible. Among these advancements are collocations which are an important aspect of foreign language learning, as they greatly enhance fluency and accuracy in language learning. The current study aims to explore the impact of collocations on the improvement of essay writing among Arabic learners as a foreign language in Nigeria. In this study, a quasi-experimental design was adopted, incorporating pre and post-test measurements. Seventy (70) undergraduate students from an intact class in the third year at the Department of Arabic during the 2022/2023 session at Umaru Musa Yar’adua University Katsina, Nigeria, were purposefully selected to participate in this essay writing training. The participants were divided into an experimental (n=35) and a control (n=35) group. During the training session, the data were collected through essay writing in pre and post-tests. An inferential statistic was employed to evaluate the significant difference between the two groups, thereby enabling the researchers to make a decision. The study found that the overall experimental group (M = 58.60, SD = 13.705) scored higher than the control group (M = 40.17, SD = 5.08). The independent sample t-test result was t (7.45), (p = .000). Therefore, there was a significant difference between the two groups. This implies that collocations play a vital role in enhancing the essay writing performance of Arabic learners as a foreign language at Umaru Musa Yar’adua University Katsina, Nigeria. It should be a great idea for instructors of Arabic as a foreign language at the Umaru Musa Yar’adua University, Katsina, Nigeria to prioritize collocations in their classroom activities, especially when teaching Arabic essay writing. The significance of the study lies in the potential of integrating collocations in the context of instructing Arabic essay writing to learners of Arabic as a foreign language. In addition, the findings can be advantageous to the university’s management by improving the Arabic syllabus and incorporating collocations to enhance the learning of Arabic essay writing. Finally, the study is beneficial to the participants because it helps them learn the Arabic language through its original forms and structure.